Family Empowerment as Nursing Intervention for Families with Type 2 Diabetes Mellitus: A Literature Review - Setyoadi; Seda, Lukas Fransiskus Saverius; Lestari, Puji; Irwando, Erdy; Nurani, Nunik; Hayati, Yati Sri; Kristianingrum, Niko Dima; Kartika, Annisa Wuri (Jurnal Kesehatan Komunitas Indonesia, 2023)
Background: This literature review is motivated by the empirical phenomenon that illustrates the increasing number of Type 2 Diabetes mellitus (T2DM) patients, which has an impact on family caregivers. The chronic condition of T2DM requires long-term care and monitoring to maintain blood glucose levels within normal limits. Family caregivers play a crucial role in assisting family members with T2DM by enhancing their roles and functions through family empowerment. Purpose: This literature review aimed to theoretically analyze the importance of family empowerment as a nursing intervention in improving the health status of family members with T2DM. Methods: The research method used in this study is a literature review, which includes an analysis of 9 articles obtained from three databases: ProQuest, Science Direct, and Google Scholar. The search keywords used for article retrieval included "family empowerment or caregiver empowerment," "diabetes mellitus," and "nursing intervention," using "AND" and "OR" as Boolean operators. Results: The literature review results show that family empowerment interventions for individuals with T2DM can be carried out by increasing knowledge, providing skills training, and enhancing family support during the care process. The success indicators for family empowerment interventions include increased self-efficacy, self-concept, self-care, and self-control for individuals with T2DM. Conclusion: The findings of this literature review demonstrate that family empowerment as a nursing intervention can yield positive outcomes for patients. Therefore, it should be considered as a reference for primary healthcare nurses to provide intervention not only to the clients but also to their families or caregivers.